Synthesis and Physicochemical Characterization of Castor Oil Methyl Ester - Batari, Nirmala Puteri; Zetra, Yulfi; Burhan, R.Y. Perry; Firdhausya, Talitha Fitra; Firdausa, Yunita Alfiyati; Putri, Rizka Berliana (Jurnal Kimia Fullerene, 2025)
The increasing consumption of biodiesel has led to the continued development of biodiesel production using oils that do not compete with food, for example castor oil. This study aims to synthesize and characterize castor oil methyl ester (COME) as biodiesel. The FFA of castor oil is 0.66%, so that a transesterification reaction with methanol using a KOH catalyst can be carried out. The reaction was characterized by Thin Layer Chromatography (TLC) and Gas Chromatography-Mass Spectrometry (GCMS). The highest content of COME is methyl ricinoleate at 65.481%. followed by FFA at 0.4%, a cloud point of -9°C, a pour point of -18°C, and a density at 40°C of 887.2 kg/m3 which is in accordance with SNI. Thus, COME has the potential as a biodiesel candidate.